2012
DOI: 10.4103/2230-8210.98012
|View full text |Cite
|
Sign up to set email alerts
|

Linear growth and neurodevelopmental outcome of children with congenital hypothyroidism detected by neonatal screening: A controlled study

Abstract: Introduction:Different growth and neuro-developmental outcomes have been associated with different doses of thyroxine given to infants with congenital hypothyroidism (CH).Materials and Methods:We studied the longitudinal growth pattern and assessed the neurodevelopment of 45 children with CH(25 girls, 20 boys) diagnosed through the national screening program in Qatar, for 6 years or more to examine the effects of initial T4 dosage (50 μg/day) with adjustment of T4 dose to maintain serum free T4 concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 14 publications
2
22
0
Order By: Relevance
“…Umbilical cord FT3 and FT4 concentrations vary widely among individuals; thus, the fetus may depend, at least in part, on maternal thyroid hormones in the third trimester [9]. This hypothesis is supported by the fact that birth weight does not differ between neonates with congenital hypothyroidism and healthy newborns [22], and serum T4 levels at birth are one-to two-thirds higher in neonates with congenital hypothyroidism than in healthy newborns [23]. Placental trophoblasts synthesize and secrete transthyretin (TTR), a thyroid hormone-binding protein [5].…”
Section: Discussionmentioning
confidence: 79%
“…Umbilical cord FT3 and FT4 concentrations vary widely among individuals; thus, the fetus may depend, at least in part, on maternal thyroid hormones in the third trimester [9]. This hypothesis is supported by the fact that birth weight does not differ between neonates with congenital hypothyroidism and healthy newborns [22], and serum T4 levels at birth are one-to two-thirds higher in neonates with congenital hypothyroidism than in healthy newborns [23]. Placental trophoblasts synthesize and secrete transthyretin (TTR), a thyroid hormone-binding protein [5].…”
Section: Discussionmentioning
confidence: 79%
“…Ashraf found no meaningful relationship between the weight of CH children and CDC healthy children. The weight growth patterns of both groups ran parallel to each other (20). Kik demonstrated that weight growth of all children with CH was within a normal range (21).…”
Section: Discussionmentioning
confidence: 94%
“…According to the study of Ashraf et al (2012), there was no considerable difference in OFC between the CH children and CDC healthy children, while children with CH had an appropriate OFC growth trend (20). Hashemipour et al reported that OFC of children with CH was smaller than that of healthy children until the age of three years (24), whereas in other studies it was shown to be larger in CH children (29).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Most studies have assessed the growth of infants with congenital hypothyroidism detected by neonatal screening. [3][4][5] Few studies have been done to assess the catch-up growth in older children with hypothyroidism. Therefore, author undertook this study to assess the catch-up growth in children with primary hypothyroidism following treatment with thyroxine.…”
Section: Introductionmentioning
confidence: 99%